Microstructure and Oxidation Behavior of NiCoCrAlY Coating With Different Sm2O3 Concentration on TiAl Alloy - Gong, X.; Chen, R. R.; Wang, Y.; Su, Y. Q.; Guo, J. J.; Fu, H. Z. (Frontiers in Materials, 2021)
In order to improve the oxidation resistance of TiAl alloys, NiCoCrAlY coatings with different amount of Sm2O3 were prepared by laser cladding on TiAl alloys. The microstructure and oxidation behavior of the coatings were investigated by isothermal oxidation tests at 900 ºC. The results indicated the grains of the coatings was refined by Sm2O3. The fine grain reduced the crack sensitivity of the doped coatings and promoted transformation of θ-Al2O3 to ɑ-Al2O3. Therefore, the internal oxidation of the coatings and the growth rate of the oxide films were reduced. The segregation of Sm at grain boundary inhibited the outward diffusion of Ti, thus reducing excessive oxidation of Ti. In addition, the oxidation mechanism of the coating was changed from simultaneous diffusion of Al and O to predominant inward diffusion of O. The oxidation resistance of the doped coatings was significantly improved. However, excessive Sm2O3 is detrimental to the improvement of the oxidation resistance. The oxidation resistance of 3 wt.% Sm2O3 is the best .